A Study on Acinetobacter spp isolated from various clinical samples and analysis of their susceptibility pattern at a tertiary care center - Mahamad Wajid; Prasanna Gonti; Saranya Mallamgunta; Shazia Naaz (Tropical Journal of Pathology and Microbiology, 2022)
Background: Among the gram-negative bacterial infections, Acinetobacter spp infections are ofcritical importance given the severity of infections, intrinsic resistance to most antibiotics, and alsocapability to acquire new drug resistance. Aim: To study the prevalence of Acinetobacter spp and itsantibiotic resistance patterns in a tertiary care hospital. Materials and methods: A retrospectivestudy, including samples from various departments, submitted to the microbiology laboratory fromJanuary 2020 to December 2020. All the samples were processed according to standardconventional methods, and the Acinetobacter isolates were studied in detail about the demographiccharacters, speciation, and antibiotic susceptibility pattern. Results: Out of the 1242 positiveisolates, 7.24 % were identified as Acinetobacter species; 90% were A. baumannii. Males were mostcommon, most commonly belonging to 45-65 yrs. Out of all the recovered Acinetobacter spp, 30%were from ICU. 40% of the isolates were MDR, 74.07% from ICU and 26.98% from non-ICU settingswere statistically significant (p <0.005). Cephalosporins showed the highest resistance to theisolates Ceftazidime 82.5%, followed by Gentamicin 73.3%. Conclusion: The present study showedthat Acinetobacter spp prevalence and antibiotic resistance (MDR) are more common in ICUs. Theemergence of carbapenem resistance in more than half the isolates is worrisome. The studysuggests susceptibility testing to be done to help select the best antimicrobial drugs for therapy,thus helping in judicial use of antibiotics is necessary to prevent the emergence of antimicrobialresistance.